PERBEDAAN ASUPAN ENERGI, MAKRONUTRIEN, STATUS GIZI, DAN VO2 MAKS ANTARA ATLET SEPAK BOLA ASRAMA DAN NON ASRAMA [The Differences of Energy, Macronutrient Intake, Nutritional Status, and VO2 Max between Boarding and Non-Boarding Football Athletes] - Ayu Alfitasari; Fillah Fithra Dieny; Martha Ardiaria; A. Fahmi Arif Tsani (Universitas Airlangga, 2019)
Football athletes require high-quality physical fitness that affects achievement. Nutritional status was the outcome of dietary intake and can influence physical fitness. Athletes who boarded have an organized eating arrangement, so the dietary intake is more assured. The objective of this study was to analyze the differences of energy, macronutrients intake, nutritional status, and V2 max between boarding and nonboarding football athletes aged 13 - 18 years. A cross-sectional study was done in 32 people who divided into two groups (boarding and non-boarding football athletes).The collected datas included food intake using 6x24 hoursfood recalls, height using microtoise, weight using digital scales, BMI for Age using WHO Anthro Plus, body fat percentage using Bioelectrical Impedance Analysis, VO2 max using Cooper Test 2.4 km. Nutrient values were analyzed using NutriSurvey. Statistical analysis using Independent TTest. There were significant differences between energy and macronutrient intake (p=0.001), body fat percentage (p=0.004), and VO2 max score (p=0.001) of boarding and non-boarding athletes. Energy and macronutrient intake of boarding and non-boarding athletes were still in the deficient category; however, the average nutritional intake of boarding athletes were still higher than non-boarding athletes. Most nutritional status of athletes based on BMI/Age were in normal category (87.5% in boarding athletes and 62.5% in non-boarding athletes). There was no over in non-boarding athlete. However, there were 12.5% of boarding athletes in the over fat category. 25% of non-boarding athletes were in the under fat category, while in boarding athletes, none of athlete in under fat category. 62.5% boarding athletes had VO2 max score at a very good level, while 87.5% of non boarding athletes were in enough category. There were significant differences between energy and macronutrient intake, body fat percentage, and VO2 max score between boarding and non-boarding football athletes.